Climatology and annual cycle of global ocean dissolved oxygen represented by multiple observational gridded products - Juan Du; Lijing Cheng; Takamitsu Ito; Hernan E. Garcia; Zhankun Wang; Jonathan D. Sharp; Christopher J. Roach; Shoshiro Minobe; Yuntao Zhou; Bin Lu; Gian Giacomo Navarra; Seth M. Bushinsky (Ocean Science, 2026)
Ocean dissolved oxygen (O2) is an essential climate variable crucial for sustaining the marine life; thus, changes of O2 at various spatiotemporal scales should be quantified and understood. Here, we study the climatology and annual cycle of O2 at regional to global scales using eight available gridded observational products. These datasets are generated by different groups using different primary data selection, quality control, bias correction, and interpolation methods, including statistical and machine-learning-based mapping methods. A common set of metrics was collaboratively developed by the community of the Gridded Observational Dataset Intercomparison Project-Dissolved Oxygen (GODIP-DO) to facilitate the inter-comparison. We find that global mean O2 profiles are consistent among all products (±3 µmol kg−1), with the well-established decrease from high surface values to a minimum ∼ 1000 m, and subsequent increase to higher O2 at depth, although local differences could reach ±25 µmol kg−1 (0–1000 m). The hemispheric O2 annual cycle correlates strongly with ocean temperature changes, suggesting the key driver of temperature for the O2 annual cycle. However, there is substantial variation in the global mean 0–100 m O2 annual cycle, the magnitude ranges from −1 to 0.8 µmol kg−1, with a standard deviation of the datasets of ∼ 0.3 µmol kg−1. Average oxygen minimum zones (OMZ) volume among the products is 80.92 × 106 km3 (±1.95 %) for a 60 µmol kg−1 threshold and 152.00 × 106 km3 (±1.72 %) for a 90 µmol kg−1 threshold. Our results help to depict and understand the spread among the available O2 gridded datasets.

Environmental identities of college students reveal potential conflicts and common ground for wildlife conservation - Richard Von Furstenberg; Lincoln R. Larson; M. Nils Peterson; Kangjae Jerry Lee; Victoria R. Vayer; kathryn stevenson; Stacy A.C. Nelson; Jeremy Bruskotter; Adam A. Ahlers; Christine Anhalt-Depies; Taniya Bethke; Chris Chizinski; et al. (Biological Conservation, 2025)

Effectiveness of steam cleaning technology on reducing the occurrence of ESKAPE organisms and Escherichia coli in the stables of an equine referral hospital - S. Sosa-Portugal; L. Dale; J. Devaney; A. Sharp; F. Malalana; D. Timofte (Journal of Equine Veterinary Science, 2025)

Review of APSIM's soil nitrogen modelling capability for agricultural systems analyses - Kirsten Verburg; Heather R. Pasley; Jody S. Biggs; Iris Vogeler; Enli Wang; Henrike Mielenz; Val O. Snow; Chris J. Smith; Chiara Pasut; Andrea D. Basche; Di He; Sotirios V. Archontoulis; et al. (Agricultural Systems, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Random and systematic uncertainty in ship‐based seawater carbonate chemistry observations - Brendan R. Carter; Jonathan D. Sharp; Maribel I. García‐Ibáñez; Ryan J. Woosley; Michael B. Fong; Marta Álvarez; Leticia Barbero; Simon L. Clegg; Regina Easley; Andrea J. Fassbender; Xinyu Li; Katelyn M. Schockman; et al. (Limnology and Oceanography, 2024)
Seawater carbonate chemistry observations are increasingly necessary to study a broad array of oceanographic challenges such as ocean acidification, carbon inventory tracking, and assessment of marine carbon dioxide removal strategies. The uncertainty in a seawater carbonate chemistry observation comes from unknown random variations and systematic offsets. Here, we estimate the magnitudes of these random and systematic components of uncertainty for the discrete open‐ocean carbonate chemistry measurements in the Global Ocean Data Analysis Project 2022 update (GLODAPv2.2022). We use both an uncertainty propagation approach and a carbonate chemistry measurement “inter‐consistency” approach that quantifies the disagreement between measured carbonate chemistry variables and calculations of the same variables from other carbonate chemistry measurements. Our inter‐consistency analysis reveals that the seawater carbonate chemistry measurement community has collected and released data with a random uncertainty that averages about 1.7 times the uncertainty estimated by propagating the desired “climate‐quality” random uncertainties. However, we obtain differing random uncertainty estimates for subsets of the available data, with some subsets seemingly meeting the climate‐quality criteria. We find that seawater pH measurements on the total scale do not meet the climate‐quality criteria, though the inter‐consistency of these measurements improves (by 38%) when limited to the subset of measurements made using purified indicator dyes. We show that GLODAPv2 adjustments improve inter‐consistency for some subsets of the measurements while worsening it for others. Finally, we provide general guidance for quantifying the random uncertainty that applies for common combinations of measured and calculated values.

Uncertainty sources for measurable ocean carbonate chemistry variables - Brendan R. Carter; Jonathan D. Sharp; Andrew G. Dickson; Marta Álvarez; Michael B. Fong; Maribel I. García‐Ibáñez; Ryan J. Woosley; Yuichiro Takeshita; Leticia Barbero; Robert H. Byrne; Wei‐Jun Cai; Melissa Chierici; et al. (Limnology and Oceanography, 2024)
The ocean carbonate system is critical to monitor because it plays a major role in regulating Earth's climate and marine ecosystems. It is monitored using a variety of measurements, and it is commonly understood that all components of seawater carbonate chemistry can be calculated when at least two carbonate system variables are measured. However, several recent studies have highlighted systematic discrepancies between calculated and directly measured carbonate chemistry variables and these discrepancies have large implications for efforts to measure and quantify the changing ocean carbon cycle. Given this, the Ocean Carbonate System Intercomparison Forum (OCSIF) was formed as a working group through the Ocean Carbon and Biogeochemistry program to coordinate and recommend research to quantify and/or reduce uncertainties and disagreements in measurable seawater carbonate system measurements and calculations, identify unknown or overlooked sources of these uncertainties, and provide recommendations for making progress on community efforts despite these uncertainties. With this paper we aim to (1) summarize recent progress toward quantifying and reducing carbonate system uncertainties; (2) advocate for research to further reduce and better quantify carbonate system measurement uncertainties; (3) present a small amount of new data, metadata, and analysis related to uncertainties in carbonate system measurements; and (4) restate and explain the rationales behind several OCSIF recommendations. We focus on open ocean carbonate chemistry, and caution that the considerations we discuss become further complicated in coastal, estuarine, and sedimentary environments.

Global patterns in endemicity and vulnerability of soil fungi - Leho Tedersoo; Vladimir Mikryukov; Alexander Zizka; Mohammad Bahram; Niloufar Hagh‐Doust; Sten Anslan; Oleh Prylutskyi; Manuel Delgado‐Baquerizo; Fernando T. Maestre; Jaan Pärn; Maarja Öpik; Mari Moora; et al. (Global Change Biology, 2022)
Fungi are highly diverse organisms, which provide multiple ecosystem services. However, compared with charismatic animals and plants, the distribution patterns and conservation needs of fungi have been little explored. Here, we examined endemicity patterns, global change vulnerability and conservation priority areas for functional groups of soil fungi based on six global surveys using a high‐resolution, long‐read metabarcoding approach. We found that the endemicity of all fungi and most functional groups peaks in tropical habitats, including Amazonia, Yucatan, West‐Central Africa, Sri Lanka, and New Caledonia, with a negligible island effect compared with plants and animals. We also found that fungi are predominantly vulnerable to drought, heat and land‐cover change, particularly in dry tropical regions with high human population density. Fungal conservation areas of highest priority include herbaceous wetlands, tropical forests, and woodlands. We stress that more attention should be focused on the conservation of fungi, especially root symbiotic arbuscular mycorrhizal and ectomycorrhizal fungi in tropical regions as well as unicellular early‐diverging groups and macrofungi in general. Given the low overlap between the endemicity of fungi and macroorganisms, but high conservation needs in both groups, detailed analyses on distribution and conservation requirements are warranted for other microorganisms and soil organisms.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Best Practice Data Standards for Discrete Chemical Oceanographic Observations - Li-Qing Jiang; Denis Pierrot; Rik Wanninkhof; Richard A. Feely; Bronte Tilbrook; Simone Alin; Leticia Barbero; Robert H. Byrne; Brendan R. Carter; Andrew G. Dickson; Jean-Pierre Gattuso; Dana Greeley; et al. (Frontiers in Marine Science, 2022)
Effective data management plays a key role in oceanographic research as cruise-based data, collected from different laboratories and expeditions, are commonly compiled to investigate regional to global oceanographic processes. Here we describe new and updated best practice data standards for discrete chemical oceanographic observations, specifically those dealing with column header abbreviations, quality control flags, missing value indicators, and standardized calculation of certain properties. These data standards have been developed with the goals of improving the current practices of the scientific community and promoting their international usage. These guidelines are intended to standardize data files for data sharing and submission into permanent archives. They will facilitate future quality control and synthesis efforts and lead to better data interpretation. In turn, this will promote research in ocean biogeochemistry, such as studies of carbon cycling and ocean acidification, on regional to global scales. These best practice standards are not mandatory. Agencies, institutes, universities, or research vessels can continue using different data standards if it is important for them to maintain historical consistency. However, it is hoped that they will be adopted as widely as possible to facilitate consistency and to achieve the goals stated above.

Correction to: Histamine, mast cell tryptase and post-exercise hypotension in healthy and collapsed marathon runners - I. T. Parsons; M. J. Stacey; L. Faconti; N. Hill; J. O’Hara; E. Walter; B. Farukh; R. McNally; H. Sharp; A. Patten; R. Grimaldi; N. Gall; et al. (European Journal of Applied Physiology, 2021)

Histamine, mast cell tryptase and post-exercise hypotension in healthy and collapsed marathon runners - I. T. Parsons; M. J. Stacey; L. Faconti; N. Hill; J. O’Hara; E. Walter; B. Farukh; R. McNally; H. Sharp; A. Patten; R. Grimaldi; N. Gall; et al. (European Journal of Applied Physiology, 2021)
Purpose Heat stress exacerbates post-exercise hypotension (PEH) and cardiovascular disturbances from elevated body temperature may contribute to exertion-related incapacity. Mast cell degranulation and muscle mass are possible modifiers, though these hypotheses lack practical evidence. This study had three aims: (1) to characterise pre–post-responses in histamine and mast cell tryptase (MCT), (2) to investigate relationships between whole body muscle mass (WBMM) and changes in blood pressure post-marathon, (3) to identify any differences in incapacitated runners. Methods 24 recreational runners were recruited and successfully completed the 2019 Brighton Marathon (COMPLETION). WBMM was measured at baseline. A further eight participants were recruited from incapacitated runners (COLLAPSE). Histamine, MCT, blood pressure, heart rate, body temperature and echocardiographic measures were taken before and after exercise (COMPLETION) and upon incapacitation (COLLAPSE). Results In completion, MCT increased by nearly 50% from baseline ( p = 0.0049), whereas histamine and body temperature did not vary ( p > 0.946). Systolic (SBP), diastolic (DBP) and mean (MAP) arterial blood pressures and systemic vascular resistance (SVR) declined ( p < 0.019). WBMM negatively correlated with $$Δ $$ Δ SBP ( r = − 0.43, p = 0.046). For collapse versus completion, there were significant elevations in MCT (1.77 ± 0.25 μg/L vs 1.18 ± 0.43 μg/L, p = 0.001) and body temperature (39.8 ± 1.3 °C vs 36.2 ± 0.8 °C, p < 0.0001) with a non-significant rise in histamine (9.6 ± 17.9 μg/L vs 13.7 ± 33.9 μg/L, p = 0.107) and significantly lower MAP, DBP and SVR ( p < 0.033). Conclusion These data support the hypothesis that mast cell degranulation is a vasodilatory mechanism underlying PEH and exercise associated collapse. The magnitude of PEH is inversely proportional to the muscle mass and enhanced by concomitant body heating.

JA:2021-31. Does the Use of a Nasal Lavage Intervention Improve Pulmonary Function for Dairy Workers? - James Seidel; Grant Erlandson; Julia D. Labadie; Sheryl Magzamen; Julia Sharp; Ken Jones; Matthew Nonnenmann; Stephen J. Reynolds; Joshua W. Schaeffer (Journal of Agromedicine, 2020)

Foundation species patch configuration mediates salt marsh biodiversity, stability and multifunctionality - Sinéad M. Crotty; Sean J. Sharp; Ada C. Bersoza; Kimberly D. Prince; Katheryne Cronk; Emma E. Johnson; Christine Angelini (Ecology Letters, 2018)
Foundation species enhance biodiversity and multifunctionality across many systems; however, whether foundation species patch configuration mediates their ecological effects is unknown. In a 6‐month field experiment, we test which attributes of foundation species patch configuration – i.e. patch size, total patch area, perimeter, area‐perimeter ratio, or connectivity – control biodiversity, stability and multifunctionality by adding a standardised density of mussel foundation species in patches of 1, 5, 10, 30, 60, 90 or 180 individuals to a southeastern US salt marsh. Over 67% of response variables increased with clustering of mussels, responses that were driven by increases in area–perimeter ratio (33%), decreases in perimeter (29%), or increases in patch size (5%), suggesting sensitivity to external stressors and/or dependence on foundation species‐derived niche availability and segregation. Thus, mussel configuration – by controlling the relative distribution of multidimensional patch interior and edge niche space – critically modulates this foundation species’ effects on ecosystem structure, stability and function.

Assessing uncertainties in crop and pasture ensemble model simulations of productivity and N 2 O emissions - Fiona Ehrhardt; Jean‐François Soussana; Gianni Bellocchi; Peter Grace; Russel McAuliffe; Sylvie Recous; Renáta Sándor; Pete Smith; Val Snow; Massimiliano de Antoni Migliorati; Bruno Basso; Arti Bhatia; et al. (Global Change Biology, 2018)
Simulation models are extensively used to predict agricultural productivity and greenhouse gas emissions. However, the uncertainties of (reduced) model ensemble simulations have not been assessed systematically for variables affecting food security and climate change mitigation, within multi‐species agricultural contexts. We report an international model comparison and benchmarking exercise, showing the potential of multi‐model ensembles to predict productivity and nitrous oxide (N 2 O) emissions for wheat, maize, rice and temperate grasslands. Using a multi‐stage modelling protocol, from blind simulations (stage 1) to partial (stages 2–4) and full calibration (stage 5), 24 process‐based biogeochemical models were assessed individually or as an ensemble against long‐term experimental data from four temperate grassland and five arable crop rotation sites spanning four continents. Comparisons were performed by reference to the experimental uncertainties of observed yields and N 2 O emissions. Results showed that across sites and crop/grassland types, 23%–40% of the uncalibrated individual models were within two standard deviations ( SD ) of observed yields, while 42 (rice) to 96% (grasslands) of the models were within 1 SD of observed N 2 O emissions. At stage 1, ensembles formed by the three lowest prediction model errors predicted both yields and N 2 O emissions within experimental uncertainties for 44% and 33% of the crop and grassland growth cycles, respectively. Partial model calibration (stages 2–4) markedly reduced prediction errors of the full model ensemble E‐median for crop grain yields (from 36% at stage 1 down to 4% on average) and grassland productivity (from 44% to 27%) and to a lesser and more variable extent for N 2 O emissions. Yield‐scaled N 2 O emissions (N 2 O emissions divided by crop yields) were ranked accurately by three‐model ensembles across crop species and field sites. The potential of using process‐based model ensembles to predict jointly productivity and N 2 O emissions at field scale is discussed.

Biomarkers of Acute Stroke Etiology (BASE) Study Methodology - Edward C. Jauch; Andrew D. Barreto; Joseph P. Broderick; Doug M. Char; Brett L. Cucchiara; Thomas G. Devlin; Alison J. Haddock; William J. Hicks; Brian C. Hiestand; Glen C. Jickling; Jeff June; David S. Liebeskind; et al. (Translational Stroke Research, 2017)

Functional neuroimaging of visuo-vestibular interaction - R. E. Roberts; H. Ahmad; Q. Arshad; M. Patel; D. Dima; R. Leech; B. M. Seemungal; D. J. Sharp; A. M. Bronstein (Brain Structure and Function, 2017)

Effects of the potential lithium-mimetic, ebselen, on impulsivity and emotional processing - Charles Masaki; Ann L. Sharpley; Charlotte M. Cooper; Beata R. Godlewska; Nisha Singh; Sridhar R. Vasudevan; Catherine J. Harmer; Grant C. Churchill; Trevor Sharp; Robert D. Rogers; Philip J. Cowen (Psychopharmacology, 2016)

Retrospective stable isotope analysis reveals ecosystem responses to river regulation over the last century - Thomas F. Turner; Trevor J. Krabbenhoft; Michael L. Collyer; Corey A. Krabbenhoft; Melanie S. Edwards; Zachary D. Sharp (Ecology, 2015)
Disruption of natural flow regimes, nutrient pollution, and other consequences of human population growth and development have impacted most major rivers of the world. Alarming losses of aquatic biodiversity coincide with human‐caused river alteration, but effects of biotic homogenization on aquatic ecosystem processes are not as well documented. This is because unaltered systems for comparison are scarce, and some ecosystem‐wide effects may take decades to manifest. We evaluated aquatic ecosystem responses to extensive river‐floodplain engineering and nutrient addition in the Rio Grande of southwestern North America as revealed by changes in trophic structure of, and resource availability to, the fish community. Stable Isotope Analysis (SIA) was conducted on museum‐preserved fishes collected over a 70‐year period of intensive river management and exponential human population growth. Trophic complexity and resource heterogeneity for fish consumers (measured as “isotopic niche breadth”) decreased following sediment deprivation and channelization, and these effects persist into the present. Increased nutrient inputs led to δ 15 N enrichment in the entire fish community at all affected sites, and a shift to autochthonous sources of carbon at the most proximal site downstream of wastewater release, probably via bottom‐up transfer. Overall, retrospective SIA of apex consumers suggests radical change and functional impairment of a floodplain river ecosystem already marked by significant biodiversity loss.

Assessing the sensitivity of habitats to fishing: from seabed maps to sensitivity maps a - N. C. Eno; C. L. J. Frid; K. Hall; K. Ramsay; R. A. M. Sharp; D. P. Brazier; S. Hearn; K. M. Dernie; K. A. Robinson; O. A. L. Paramor; L. A. Robinson (Journal of Fish Biology, 2013)
In the Welsh part of the Irish Sea, a method was developed for assessing the sensitivity of different seabed habitats to existing fishing activities, across a range of potential fishing intensities. The resistance of 31 habitats and their associated biological assemblage to damage by 14 categories of fishing activity were assessed along with the rate at which each habitat would recover following impact (resilience). Sensitivity was scored based on a combination of the resistance of a habitat to damage and its subsequent rate of recovery. The assessments were based, wherever possible, on scientific literature, with expert judgement used to extrapolate results to habitat and gear combinations not directly examined in the published literature. The resulting sensitivity matrices were then subject to further peer review at a series of workshops. Following consensus on the habitat sensitivity, these data were combined with the most resolved sea‐floor habitat maps. These habitat sensitivity maps can help inform the development of site‐specific management plans, as well as having a place in spatial planning and aiding managers in developing dialogue with other stakeholders. A case study of their application is provided.

A simple temperature-based model predicts the upper latitudinal limit of the temperate coral Astrangia poculata - J. L. Dimond; A. H. Kerwin; R. Rotjan; K. Sharp; F. J. Stewart; D. J. Thornhill (Coral Reefs, 2013)

Apical-Ventricular Cannula for Aortic Valve Bypass Therapy - Kevin G. Soucy; Joel D. Graham; Carrie J. Benzinger; M. Keith Sharp; Guruprasad A. Giridharan; Michael A. Sobieski; Mark S. Slaughter; Steven C. Koenig (Cardiovascular Engineering and Technology, 2013)

Variability and change in the Canadian cryosphere - C. Derksen; S. L. Smith; M. Sharp; L. Brown; S. Howell; L. Copland; D. R. Mueller; Y. Gauthier; C. G. Fletcher; A. Tivy; M. Bernier; J. Bourgeois; et al. (Climatic Change, 2012)
During the International Polar Year (IPY), comprehensive observational research programs were undertaken to increase our understanding of the Canadian polar cryosphere response to a changing climate. Cryospheric components considered were snow, permafrost, sea ice, freshwater ice, glaciers and ice shelves. Enhancement of conventional observing systems and retrieval algorithms for satellite measurements facilitated development of a snapshot of current cryospheric conditions, providing a baseline against which future change can be assessed. Key findings include: 1. surface air temperatures across the Canadian Arctic exhibit a warming trend in all seasons over the past 40 years. A consistent pan-cryospheric response to these warming temperatures is evident through the analysis of multi-decadal datasets; 2. in recent years (including the IPY period) a higher rate of change was observed compared to previous decades including warming permafrost, reduction in snow cover extent and duration, reduction in summer sea ice extent, increased mass loss from glaciers, and thinning and break-up of the remaining Canadian ice shelves. These changes illustrate both a reduction in the spatial extent and mass of the cryosphere and an increase in the temporal persistence of melt related parameters. The observed changes in the cryosphere have important implications for human activity including the close ties of northerners to the land, access to northern regions for natural resource development, and the integrity of northern infrastructure.

Methanogenic potential of Arctic and Antarctic subglacial environments with contrasting organic carbon sources - Marek Stibal; Jemma L. Wadham; Grzegorz P. Lis; Jon Telling; Richard D. Pancost; Ashley Dubnick; Martin J. Sharp; Emily C. Lawson; Catriona E. H. Butler; Fariha Hasan; Martyn Tranter; Alexandre M. Anesio (Global Change Biology, 2012)
Subglacial environments are largely anoxic, contain organic carbon ( OC ) overridden by glacier ice during periods of advance, and harbour active microbial communities. This creates favourable conditions for OC degradation via methanogenesis. It has been hypothesized that OC beneath ice sheets is converted to methane ( CH 4 ) and may be released to the atmosphere during retreat. However, there are limited data available to support this contention. Here, we present new data on the abundance, diversity and activity of methanogenic archaea and the amount and character of OC in subglacial sediments from Arctic and Antarctic glacial systems based on different substrate types. We employed long‐term laboratory incubations to quantify the CH 4 production potential in different subglacial settings. Significant numbers of methanogens (up to 7 × 10 4 cells g −1 ) were detected in the samples and clones of Methanomicrobiales and Methanosarcinales were identified in clone libraries. Long lag periods (up to >200 days) were observed before significant CH 4 concentrations were measured. We report order of magnitude differences in rates of CH 4 production (10 1 –10 5 fmol g −1 d −1 ) in different subglacial sediments, reflecting contrasts in the origin of the sediment and the OC character. Hence, we predict that contrasting rates of CH 4 production are likely to occur beneath glaciers and ice sheets that overran different types of substrate. We subsequently estimated the potential for CH 4 production beneath the Laurentide/Inuitian/Cordilleran and Fennoscandian Ice Sheets during a typical 85 ka Quaternary glacial/interglacial cycle. CH 4 production from lacustrine‐derived OC is likely to be an order of magnitude higher (~6.3–27 Pg C) than that from overridden soils (~0.55–0.68 Pg C), possibly due to a difference in lability between lacustrine and soil OC . While representing a fraction of the entire OC pool (~418–610 Pg C), this finding highlights the importance of considering the character of different OC pools when calculating subglacial CH 4 production.

An Integrated WebGIS Framework for Volunteered Geographic Information and Social Media in Soil and Water Conservation - Joshua D. Werts; Elena A. Mikhailova; Christopher J. Post; Julia L. Sharp (Environmental Management, 2012)

The Changing Arctic Cryosphere and Likely Consequences: An Overview - M. S. Olsen; T. V. Callaghan; J. D. Reist; L. O. Reiersen; D. Dahl-Jensen; M. A. Granskog; B. Goodison; G. K. Hovelsrud; M. Johansson; R. Kallenborn; J. Key; A. Klepikov; et al. (Ambio, 2011)

Gender-Dependent Correlations of Carotid Intima–Media Thickness with Gene Expression in Blood - Renée J. Turner; Cheryl D. Bushnell; Thomas C. Register; Frank R. Sharp (Translational Stroke Research, 2011)

Impact of PSA testing and prostatic biopsy on cancer incidence and mortality: comparative study between the Republic of Ireland and Northern Ireland - A-E. Carsin; F. J. Drummond; A. Black; P. J. van Leeuwen; L. Sharp; L. J. Murray; D. Connolly; L. Egevad; M. Boniol; P. Autier; H. Comber; A. Gavin (Cancer Causes & Control, 2010)

Development and genetic mapping of sequence-tagged microsatellites (STMs) in bread wheat (Triticum aestivum L.) - M. J. Hayden; P. Stephenson; A. M. Logojan; D. Khatkar; C. Rogers; J. Elsden; R. M. D. Koebner; J. W. Snape; P. J. Sharp (Theoretical and Applied Genetics, 2006)

Aromatase inhibition abolishes courtship behaviours in the ring dove (Streptopelia risoria) and reduces androgen and progesterone receptors in the hypothalamus and anterior pituitary gland - M. D. C. Belle; P. J. Sharp; R. W. Lea (Molecular and Cellular Biochemistry, 2005)

Nuclear BAG-1 expression inhibits apoptosis in colorectal adenoma-derived epithelial cells - J. D. Barnes; N. J. Arhel; S. S. Lee; A. Sharp; M. Al-Okail; G. Packham; A. Hague; C. Paraskeva; A. C. Williams (Apoptosis, 2005)

Isotopic ( 13 C and 14 C) evidence supporting the transformative effect of cattle on north Australian vegetation - D. M. J. S. Bowman; B. R. Sharp; U. Zoppi (Journal of Biogeography, 2004)

A new approach to extending the wheat marker pool by anchored PCR amplification of compound SSRs - M. J. Hayden; P. Stephenson; A. M. Logojan; D. Khatkar; C. Rogers; R. M. D. Koebner; J. W. Snape; P. J. Sharp (Theoretical and Applied Genetics, 2004)

Fasting differentially regulates expression of agouti-related peptide, pro-opiomelanocortin, prepro-orexin, and vasoactive intestinal polypeptide mRNAs in the hypothalamus of Japanese quail - D. Phillips-Singh; Q. Li; S. Takeuchi; T. Ohkubo; P. J. Sharp; T. Boswell (Cell and Tissue Research, 2003)

FURTHER CHARACTERIZATION OF BC3H1 MYOGENIC CELLS REVEALS LACK OF P53 ACTIVITY AND UNDEREXPRESSION OF SEVERAL P53 REGULATED AND EXTRACELLULAR MATRIX–ASSOCIATED GENE PRODUCTS - SANDRA B. SHARP; MARIA VILLALVAZO; MICKEY HUANG; RODOLFO GONZALEZ; IRANIA ALARCON; MATTHEW BAHAMONDE; DIANE M. D'AGOSTIN; SAGAR DAMLE; ALEX ESPINOSA; SEOG J. HAN; JESSICA LIU; PAULA NAVARRO; et al. (In Vitro Cellular & Developmental Biology - Animal, 2002)

Comparison of microbial populations in model and natural rumens using 16S ribosomal RNA‐targeted probes - Cherie J. Ziemer; Richard Sharp; Marshall D. Stern; Michael A. Cotta; Terence R. Whitehead; David A. Stahl (Environmental Microbiology, 2000)
A model rumen system, dual‐flow continuous culture fermenters, was evaluated by two comparative criteria in two experiments using ribosomal (r)RNA‐targeted DNA probes to compare key microbial groups in samples. The initial experiment measured temporal changes in population structure during adaptation of ruminal microbial populations in fermenters over 240 h. The fermenter inoculum contained 34.9% Bacteria, 60.1% Eukarya and 6.8% Archaea measured as a fraction of total small subunit (SSU) rRNA quantified using a universal probe. The cellulolytic bacterial genus Fibrobacter comprised 9.5% of total SSU rRNA in the inoculum. After 240 h of fermenter operation, the average abundance was 80.9% Bacteria, 6.1% Eukarya, 5.1% Archaea and Fibrobacter genus accounted for 6.6% of the total SSU rRNA. Divergence between ruminal and fermenter population structure was evaluated in the second experiment and samples were classified as ruminal, inoculum or fermenter (96, 120, 144 and 168 h of fermenter operation). Fermenter samples had higher relative abundances of Bacteria (84.5%) and Archaea (2.1%) and lower relative abundances of Eukarya (1.8%) than ruminal samples (average 48.0% Bacteria, 1.3% Archaea and 61.5% Eukarya). The relative abundance of Fibrobacter was similar in all samples, averaging 2.5%. The ruminal and fermenter samples had similar proportions of F. succinogenes and F. succinogenes subgroup 3 (as a percentage of Fibrobacter SSU rRNA). Fibrobacter succinogenes subgroup 1 and F. intestinalis proportions of Fibrobacter were lower in fermenter samples (8.2% and 0.7% respectively) than in ruminal samples (28.4% and 2.2% respectively). Fermenters were able to maintain a core prokaryotic community structure similar to the native microbial community in the rumen. Although protozoa populations were lost, maintenance of Fibrobacter and archaeal populations indicated that the model system supported a functional community structure similar to the rumen. This model rumen system may serve as a suitable tool for studying aspects of ruminal microbial ecology and may resolve some of the relationships between microbial community structure and function by providing control of experimental conditions.

A microbiological survey of Montserrat Island hydrothermal biotopes - Tony Atkinson; Steven Cairns; D. A. Cowan; Michael J. Danson; David W. Hough; D. Barrie Johnson; Paul R. Norris; Neil Raven; Clare Robinson; Rob Robson; Richard J. Sharp (Extremophiles, 2000)

Chromosome aberrations in wheat nullisomic-tetrasomic and ditelosomic lines - K. M. Devos; M. E. Sorrells; J. A. Anderson; T. E. Miller; S. M. Reader; A. J. Lukaszewski; J. Dubcovsky; P. J. Sharp; J. Faris; M. D. Gale (Cereal Research Communications, 1999)

Influence of Gravity on Cardiac Performance - George M. Pantalos; M. Keith Sharp; Stewart J. Woodruff; D. Sean O’Leary; Richard Lorange; Scott D. Everett; Thomas E. Bennett; Thomas Shurfranz (Annals of Biomedical Engineering, 1998)